IBM PEMBANGUNAN PARIWISATA BERKELANJUTAN PAKET WISATA OUTBOND INGKUNG KWALI DI DUSUN KALAKIJO - Fadia Fitriyanti; Yordan Gunawan (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2019)
Abstract. The Kalakijo Community has recently established a Tourism Centre, which functions as a traditional culinary center for Javanese Chicken Culinary "Ingkung Kuali." Based on the participatory mapping and inquiries with the Kalakijo Community, some main issues needed to be addressed for the development of the Kalakijo Tourism Village. The issues are namely: 1. the need to develop foreign language skills for local youth community henceforth shall be referred to "Karang Taruna" and 2. to increase the marketing of Ingkung Kuali outbound package. The intended target and outcomes of the above are 1. English language skill training for the Karang Taruna as many as 6-8 youths for three days from 24 - 26 September 2016 at night located in the Karang Taruna office, Dusun Kalakijo. 2. Based on the discussion with the Ingkung Kuali Outbound tourism package marketing unit, it is found that there are a networking problem or the lack thereof, the problems currently facing the marketing unit. Therefore, with the Universitas Muhammadiyah Yogyakarta vast network, we are doing a promotion excursion to 23 Muhammadiyah Elementary throughout Sleman Regency, Yogyakarta, and Bantul Regency in August 2016. The implementation method for the Ibm Sustainable Tourism Development of Kuali Ingkung Outbound Tourism is the English language skills training for Kalakijo Karang Taruna and the expansion of the promotion of Ingkung's Outbound activities to 23 Muhammadiyah Elementary Schools throughout Sleman Regency, Yogyakarta, and Bantul Regency. The result shows that the Kalakijo Karang Taruna has gotten a basic understanding of Basic-English skills, such as the understanding of making active and passive sentences from the present tense, future tense, past tense, and present perfect tense in the form of writing and speaking. The marketing and promotion expansions of outbound tourism packages through the establishment of a network to various Muhammadiyah Elementary Schools throughout Sleman Regency, Yogyakarta, and Bantul Regency.Keywords: Sustainable tourism, tourism package, outbound Abstrak. Saat ini masyarakat Kalakijo telah mendirikan Pusat Wisata (Tourism Centre) yang sekaligus berfungsi sebagai pusat kuliner Ingkung Kwali. Berdasarkan pemetaan secara partisipatif dengan masyarakat, beberapa permasalahan yang dihadapi dalam rangka Kampung Wisata Kalakijo adalah sebagai berikut: 1.Pemberdayaan ketrampilan bahasa bagi Karang Taruna, 2.Peningkatan pemasaran paket outbond  Ingkung Kuali. Target dan luaran sebagai berikut : 1.Pelatihan ketrampilan berbahasa Inggris bagi pemuda karang taruna berjumlah 6-8 orang berlangsung selama 3 hari mulai tanggal 24 sampai dengan 26 September 2016 bertempat di Kantor Karang Taruna Dusun Kalakijo di malam hari. 2.Berdasarkan diskusi dengan unit pemasaran paket outbond  Ingkung Kuali, ada persoalan pemasaran sehingga dengan jaringan yang dimiliki oleh UMY, kami melakukan promosi kegiatan outbond Ingkung Kuali ke 23 SD Muhammadiyah dilingkungan DIY yaitu sekitar Kabupaten Sleman, Kota Yogyakarta dan Kabupaten Bantul pada bulan Agustus 2016. Metode pelaksanaan pengabdian Ibm Pembangunan Pariwisata Berkelanjutan Paket Wisata Outbond Ingkung Kwali di Dusun Kalakijo ini meliputi 1) pelatihan bahasa Inggris bagi pemuda Karang Taruna Dusun Kalakijo, 2) Perluasan Jasa Promosi Kegiatan Outbond Dusun Kalakijo ke 23 SD Muhammadiyah dilingkungan DIY yaitu sekitar Kabupaten Sleman, Kota Yogyakarta, dan Kabupaten Bantul. Hasil Kegiatan Pengabdianini adalah 1) Pemuda Karang Taruna Dusun Kalakijo memperoleh pemahaman membuat kalimat aktif dan pasif dari tenses Present Tense, Future Tense, Past Tense, Present Perfect Tense dalam writing dan speaking 2) Memperluas pemasaran dan promosi paket Outbond melalui jaringan SD Muhammadiyah se Kabupaten Sleman, Kabupaten Bantul dan Kota Yogyakarta.Kata Kunci: Parawisata berkelanjutan, paket wisata, outbound